The Influence of Motivation and Work Environment on Employee Performance Mediated by Job Satisfaction at the Public Appraisal Services Firm Andi Tiffani and Partners - Kurnianto Kurnianto; Kasmari Kasmari (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of work motivation and the work environment on employee performance, with job satisfaction serving as a mediating variable, at the Public Appraisal Services Firm (KJPP) Andi Tiffani & Partners. The study employs a quantitative approach with a causal design. The research population consists of 53 employees, all of whom were included in the sample using a saturated sampling technique. Data were collected via a four-point Likert scale questionnaire and analyzed using the PLS-SEM method with SmartPLS. The results indicate that respondents' perceptions regarding work motivation, the work environment, job satisfaction, and employee performance fall within the "fairly good" to "good" categories. All research indicators were found to be valid and reliable based on outer model testing. The findings suggest that enhancing work motivation and the quality of the work environment can foster job satisfaction and drive improvements in employee performance.